Adding Two Antimicrobial Glasses to an Endodontic Sealer to Prevent Bacterial Root Canal Reinfection: An In Vivo Pilot Study in Dogs - Álvaro Zubizarreta-Macho; Cristina Rico-Romano; María Jesús Fernández-Aceñero; Jesús Mena-Álvarez; Belén Cabal; Luis Antonio Díaz; Ramón Torrecillas; José Serafín Moya; Roberto López-Píriz (MDPI AG, 2021)
Current endodontic procedures continue to be unsuccessful for completely removing pathogens present inside the root canal system, which can lead to recurrent infections. In this study, we aimed to assess the antimicrobial capacity and tissue response of two inorganic bactericidal additives incorporated into a paste root canal sealer on contaminated root dentin in vivo. An experimental study was performed in 30 teeth of five Beagle dogs. After inducing microbiological contamination, root canal systems were treated by randomly incorporating one of two antimicrobial additives into a commercial epoxy-amine resin sealer (AH Plus), i.e., G3T glass-ceramic (n = 10) and ZnO-enriched glass (n = 10); 10 samples were randomized as a control group. After having sacrificed the animals, microbiological, radiological, and histological analyses were performed, which were complemented with an in vitro bactericidal test and characterization by field emission scanning electron microscopy. The tested groups demonstrated a non-significant microbiological reduction in the postmortem periapical index values between the control group and the bactericidal glass-ceramic group (p = 0.885), and between the control group and the ZnO-enriched glass group (p = 0.169). The histological results showed low values of inflammatory infiltrate, and a healing pattern characterized by fibrosis in 44.4% of the G3T glass-ceramic and 60.0% of ZnO-enriched glass. Bactericidal glassy additives incorporated in this root canal sealer are safe and effective in bacterial reduction.